1999
DOI: 10.1046/j.1365-2567.1999.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

l‐selectin expression on thymic emigrants defines two distinct tissue‐migration pathways

Abstract: SUMMARYWe have studied the appearance and phenotype of recent thymic emigrants in blood, spleen and lymph nodes (LN) of neonatal lambs. Using in situ labelling of thymocytes with¯uoroscein isothiocyanate (FITC), we examined the expression of the LN homing receptor L-selectin on ab and cd subsets of recent thymic emigrants 24 hr after labelling. There were marked differences in the proportions of CD4 + , CD8 + and cd T-cell receptor (TCR + ) cells exported from the thymus to spleen compared to lymph nodes. Sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This may be of particular relevance as we found two different subpopulations of SP CD8 emigrants, one expressing CD62L low and the other CD62L high . It has been previously reported that two main subpopulations of SP CD8 thymic emigrants exist, each expressing different levels of L-selectin and characterized by a different homing commitment (32,33). In addition, our data show that DP thymocytes are able to emigrate from fetal thymi at early but not at late-stage culture.…”
Section: Retained Cxcr4supporting
confidence: 66%
“…This may be of particular relevance as we found two different subpopulations of SP CD8 emigrants, one expressing CD62L low and the other CD62L high . It has been previously reported that two main subpopulations of SP CD8 thymic emigrants exist, each expressing different levels of L-selectin and characterized by a different homing commitment (32,33). In addition, our data show that DP thymocytes are able to emigrate from fetal thymi at early but not at late-stage culture.…”
Section: Retained Cxcr4supporting
confidence: 66%
“…However, only the CD44 molecule met this expectation [47]: 60% of the cells were positive for CD44 among RTE, about 80% among naive T cells, and nearly 100% among memory T cells. As in mice [25, 48] and sheep [49], most of the CD4 + RTE in rat are l ‐selectin positive and ICAM‐1 negative, an expression pattern comparable to that of naive CD4 + T cells. Surprisingly, the expressions of α 4 ‐integrin, LFA‐1, and IL2R on RTE are different from the expression of naive T cells, and closely resembles that of memory T cells.…”
Section: Discussionmentioning
confidence: 81%
“…We have shown previously in neonatal lambs that there are two separate populations of thymic emigrants which display distinct tissue-specific homing pathways to spleen and LN [41]. The overwhelming majority of the spleen-homing emigrants were CD8 + L-selectin -T cells, whereas the LN-homing emigrants were predominantly CD4 + T cells which did express Lselectin [42]. It seems very unlikely that thymic emigrants migrated randomly to the fetal spleen and were then selectively retained, because the migration of emigrants to the spleen occurred with such exquisite specificity.…”
Section: Discussionmentioning
confidence: 89%
“…Peripheral tissue suspensions were prepared and stained as previously described [42]. Unlabeled thymocytes were stained using biotinylated anti-CD4 mAb + anti-CD8-FITC or biotinylated anti-TCRcd mAb, followed by streptavidin-allophycocyanin (SA-APC; BD Biosciences).…”
Section: Staining and Analysis Of Thymic Emigrantsmentioning
confidence: 99%